השיר הגנוב: לאה גולדברג מתכתבת עם גנסין [ועם ציךה דראפקין] בספרה מכתבים מנסיעה מדומה - מרין תמר (מכאן, 2016)
This article explores Hebrew poet Lea Goldberg’s first book of prose fiction, Letters from an Imaginary Journey (1937). The book, an epistolary novel written during Goldberg’s first years in the land of Israel, documented Goldberg’s own journey from Europe to Israel, as well as her transition from European literature to Hebrew literature, and from poetry to prose fiction. The article focuses on the literary correspondences that stand at the heart of the book: on one hand, the correspondence between Goldberg’s protagonist, Ruth, who is striving to become a Hebrew poet, and Emanuel, her lover; on the other hand, the meta-poetic correspondence between Goldberg and Uri Nissan Gnessin, whose novella Etzel (Beside), evoked by Goldberg, reveals a literary correspondence between Gnessin himself and another female writer, Russian and Yiddish poet Ceilia Dropkin. The article addresses the poetic, ideological and gender aspects of these complex literary correspondences, which shaped and molded Lea Goldberg’s prose fiction, while casting a new light on the dialogic relations between Hebrew literature and European literature, between female writing and the Hebrew male canon, between poetry and prose fiction.